Seasonal and Spatial Differences in Feeding Ecology and Behavior of the African Civet Civettictis Civetta in Arba Minch Forest, Arba Minch, Ethiopia (Global Journal of Human-Social Science, 2015)
Feeding ecology and behavior of the African Civet (Civettictis civetta) was studied to reveal the feeding habit and behavior in Arba Minch Forest. This study include both wet and dry seasons. This study was carried out by direct and indirect observations. Direct observation was carried out during night using night visionscope. Indirect observations were made by analysing faecal samples. There were seasonal variations in the items consumed by the African Civet. They were omnivorous generalists as per the findings of the present study.
Keywords: diet; faecal analysis; generalists